1997
DOI: 10.1002/(sici)1096-8644(199702)102:2<283::aid-ajpa9>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Model for the examination of evolutionary trends in tooth development

Abstract: Through the use of serial computerized tomography (C-t) scans, two distinct developmental stages can be identified in mature teeth. C-t scans thus provide a non-destructive method for assessing growth within individual teeth, as well as for comparison of the development of modern and fossil teeth. The second deciduous molar (DM2) and first permanent molar (M1) resemble one another morphologically, despite differences in size and developmental rates. Thus, they provide an excellent model for studying variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 43 publications
3
33
0
1
Order By: Relevance
“…When these findings are considered together with those for individuals with Turner and Klinefelter syndromes, it seems that there is a definite trend in the relationship of the buccal and lingual cusps of premolar teeth, with intercuspal distances diverging as enamel thickness increases in association with additional X chromosomes (Townsend and Alvesalo, 1999). Three-dimensional analyses of occlusal surfaces and dentino-enamel junctions of extracted human teeth have confirmed that molar cusp tips tend to diverge as enamel thickness increases (Kanazawa et al, 1987), as have more recent computerized tomography studies of fossil hominid teeth (Smith et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…When these findings are considered together with those for individuals with Turner and Klinefelter syndromes, it seems that there is a definite trend in the relationship of the buccal and lingual cusps of premolar teeth, with intercuspal distances diverging as enamel thickness increases in association with additional X chromosomes (Townsend and Alvesalo, 1999). Three-dimensional analyses of occlusal surfaces and dentino-enamel junctions of extracted human teeth have confirmed that molar cusp tips tend to diverge as enamel thickness increases (Kanazawa et al, 1987), as have more recent computerized tomography studies of fossil hominid teeth (Smith et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Smith et al [9] quantified the differences in EDJ and OES sizes and shapes of the mandibular second deciduous molars and first permanent molars by calculating intercusp distances, although the resolution was not high (1.2 mm). They noted that the increase in intercusp distance at the OES was caused not by an increase in enamel thickness but rather a difference in cusp angulation, which has been confirmed using high-resolution mCT [10].…”
Section: Size and Shape Quantificationmentioning
confidence: 99%
“…From these studies, Butler suggested that cell proliferation and furrow formation continue in adjacent regions, so that the relative height and distance between cusps may change and additional cusps and invaginations appear following the onset of calcification. More recently, Smith et al (1997) demonstrated differences in angulation between cusps and proposed that their angulation reflects the spatial and temporal ordering of cell division and differentiation.…”
Section: Discussionmentioning
confidence: 76%
“…It appears that deciduous teeth grow faster than permanent teeth but have smaller, less densely arranged enamel prisms (Shellis, 1984). This rapid pattern of growth is also seen in fossil teeth (Bromage and Dean, 1985;Beynon and Wood, 1986;Dean et al, 1986;Beynon and Dean, 1987;Ramirez Rozzi, 1993;Smith, 1991;Smith et al, 1997).…”
Section: Introductionmentioning
confidence: 99%